Coronary Artery Calcification and Its Progression in Cancer Patients - Whitlock, Matthew C. (Wake Forest University, 2015)
Research over the last several decades has demonstrated that cancer and its corresponding therapies are associated with an increased risk of ischemic heart disease in cancer survivors as compared to the general population. Though several mechanisms have been proposed, the reasons for this association have not been completely elucidated. Atherosclerosis, a complex pathologic process that can involve the coronary arteries, is the most common cause of ischemic heart disease and research has suggested cancer and its therapies may be involved in its development.
Keywords: cardio-oncology; cardiotoxicity; coronary artery calcium; subclinical atherosclerosis